2020
DOI: 10.4102/phcfm.v12i1.2259
|View full text |Cite
|
Sign up to set email alerts
|

Child functioning and disability in children living with human immunodeficiency virus in a semi-rural healthcare setting in South Africa

Abstract: Background: Children living with HIV (CLHIV) often experience HIV-related impairment and disability.Aim: The study sought to understand the level of child functioning and access to rehabilitative care in the context of South African healthcare in order to inform an integrated rehabilitative framework.Setting: District level semi-rural healthcare facility in KwaZulu-Natal.Methods: The Washington Group/United Nations International Children’s Emergency Fund Module on Child Functioning, was administered to carers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This study used a quantitative cross-sectional design using the Zarit Burden Interview (ZBI) to measure the perceived care burden among caregivers of CLHIV between the ages of 5 and 10 years, accessing care at a single-site, district-level hospital in a semi-rural setting in KwaZulu-Natal. A disability prevalence study at the study setting 14 revealed that a large number of children aged 5-10 years living with HIV were experiencing disabilities. Using non-probability sampling, caregivers of 58 children between the ages of 5 and 10 years, accessing care at this study site, were recruited during their routine monthly HIV clinic visits to the hospital.…”
Section: Methodsmentioning
confidence: 99%
“…This study used a quantitative cross-sectional design using the Zarit Burden Interview (ZBI) to measure the perceived care burden among caregivers of CLHIV between the ages of 5 and 10 years, accessing care at a single-site, district-level hospital in a semi-rural setting in KwaZulu-Natal. A disability prevalence study at the study setting 14 revealed that a large number of children aged 5-10 years living with HIV were experiencing disabilities. Using non-probability sampling, caregivers of 58 children between the ages of 5 and 10 years, accessing care at this study site, were recruited during their routine monthly HIV clinic visits to the hospital.…”
Section: Methodsmentioning
confidence: 99%